PENGARUH STRATEGI PEMASARAN USAHA JASA WEDDING ORGANIZER TERHADAP KEPUASAN KONSUMEN PADA UD. JULIA PELAMINAN PEKANBARU - Eka Komalasari; Julia Wulandari (UIR Press, 2022)
This research was aimed to find out and analyze the influence of marketing strategy of the wedding organizer service business to customer satisfaction at UD. Julia Pelaminan Pekanbaru. This research is a descriptive research with a quantitative approach. This study took place at UD. Julia Courtyard Pekanbaru. The population in this study were 42 consumers. The type of data used consists of primary data and secondary data. To obtain data by means of observation, interviews and questionnaires. In analyzing the data the author uses a simple regression formula. The results of the study concluded that the value of correlation and determination (R2) was 0.992 or 99.20% according to the standard of the Guilford category. The influence of service business marketing strategy on satisfaction is 0.984 or 98.40% while 1.60% is influenced by other factors not examined in this study. Result of calculated F (2510,337) > F table (1,481) with Sig. (0.000) < 0.05. This means that the independent variables (service marketing strategy) together have a significant effect on the independent variable (consumer satisfaction).